On the Design of Public Infrastructure procurements - Arno Van Der Vlist; Sander Hardeman (European Regional Science Association (ERSA), 2010)
Public procurement of infrastructure has been subject to a long standing debate concerning the procurements' qualification requirements. Basically, it remains unclear what determines public procurement officers to vary procurements' qualification requirements. This research serves to elaborate on public procurements' procedure design. The aim of this paper is to improve our understanding of why contracting authorities choose specific requirements prior to public procurement. What determines variation in public procurements' qualification requirements? For this the procurements' procedure design is modelled as a rational choice among a set of alternatives within a random utility framework. Qualification requirements are chosen as to maximize utility of the procurements' officer. In the empirical part of the paper the procurements' procedure design is modelled as a limited dependent variable model. The data comes from the EIB Monitor Procurements covering public procurements in the Netherlands, and relates to public open procurements of civil work posted by municipalities in the first half of 2009. The model results indicate that requirements do relate to degree of professionalism of the procurement office and to the type of work. These results indicate a rational choice among qualification requirements yet explain about 15 percent of total variation, suggesting other factors at work.
Keywords: 330; Construction industry; infrastructure; Bidding; Public Procurement Auctions; municipalities